A feasibility study on non-invasive fetal ECG to evaluate prenatal autonomic nervous system activity. (March 2020) - Mannella, Paolo; Billeci, Lucia; Giannini, Andrea; Canu, Alessio; Pancetti, Federica; Simoncini, Tommaso; Varanini, Maurizio
Abstract: Background: Maturity of the autonomic nervous system (ANS) is of paramount importance for fetal adaptation to extrauterine life and for early neurological development. Markers of ANS maturity, such as electrophysiological heart rate parameters, are of interest as tools to determine prenatal fetal maturity. The available technology, fetal magnetocardiography is expensive and not suitable for clinical use. Detection of fetal electrocardiographic signals using traditional ECG leads on the maternal abdomen may be brought to the bedside, but is technically challenging. Our group has recently developed an innovative system consisting of a standard ECG with external leads applied on the maternal abdomen coupled with a software that extracts the fetal heart signal from the maternal noise. Objective: To validate the use of this innovative non-invasive system to detect fetal ECG (fECG) and its ability to detect changes in electrophysiological fetal cardiac parameters associated with ANS maturation. Study design: we recruited 50 pregnant women between 24 and 41 weeks and they received non-invasive recording of fECG. Results: fECG was measurable at all gestational ages. Fetal heart rate variability (RR interval) and other associated parameters, such as low and high frequency increased with gestational age, particularly up to the 31st week. Conclusions: This study shows that non-invasive fECG is feasible throughout a broad range of gestational ages and allows detecting electrophysiological parameters of the fetal heart that may be used a surrogate of ANS maturity. Technological implementation of this system and its further exploitation may generate new tool to estimate fetal maturity.